Extração automática de contornos de telhados usando dados de varredura a laser e campos randômicos de Markov - Dos Santos Galvanin, Edineia Aparecida [UNESP]; Dal Poz, Aluir Porfírio [UNESP]; Pires de Souza, Aparecida Doniseti [UNESP] (Universidade Federal do Paraná (UFPR), Centro Politecnico, 2008)
This paper proposes a methodology for automatic extraction of building roof contours from a Digital Elevation Model (DEM), which is generated through the regularization of an available laser point cloud. The methodology is based on two steps. First, in order to detect high objects (buildings, trees etc.), the DEM is segmented through a recursive splitting technique and a Bayesian merging technique. The recursive splitting technique uses the quadtree structure for subdividing the DEM into homogeneous regions. In order to minimize the fragmentation, which is commonly observed in the results of the recursive splitting segmentation, a region merging technique based on the Bayesian framework is applied to the previously segmented data. The high object polygons are extracted by using vectorization and polygonization techniques. Second, the building roof contours are identified among all high objects extracted previously. Taking into account some roof properties and some feature measurements (e. g., area, rectangularity, and angles between principal axes of the roofs), an energy function was developed based on the Markov Random Field (MRF) model. The solution of this function is a polygon set corresponding to building roof contours and is found by using a minimization technique, like the Simulated Annealing (SA) algorithm. Experiments carried out with laser scanning DEM's showed that the methodology works properly, as it delivered roof contours with approximately 90% shape accuracy and no false positive was verified.
Automatic extraction of building roof contours by laser scanning data and markov random field
Keywords: Automatic Extraction; Building Roof Contours; Digital Elevation Model; Laser Scanning Data; Markov Random Field